The Effect Of Experimental Methods And Instructional Learning Models On Creativity And Learning Outcomes Thematic For Grade V Students - Andi Indah Angraeni; Mulyadi Mulyadi; Erwin Nurdiansyah (ALENA : Journal of Elementary Education, 2026)
The development of thematic learning requires teachers to apply approaches that can develop creativity while improving student learning outcomes. One approach that is considered relevant is the experimental method combined with the constructive learning model, because both emphasize meaningful learning activities and direct experience. Based on this background, this study aims to describe the application of the influence of the experimental method and the constructive learning model on the creativity and thematic learning outcomes of fifth-grade students at SDN 80 Kuri Lompo. This study uses a quantitative approach through a quasi-experimental Nonequivalent Control Group Design. The research sample consisted of 25 students selected using a purposive sampling technique. Data were collected through observation, questionnaires, tests, and documentation, then analyzed using normality tests, homogeneity, T-Test, and Mann-Whitney U Test. Learning success was measured through the implementation of learning and an increase in learning outcomes of at least 75% according to the Minimum Completion Minimum (KKM). The results showed that the average initial ability of students was 72.4 with 56% completeness. After the application of the experimental method and constructive learning, the average learning outcome increased to 86 with 88% classical completeness. Statistical tests showed a significant difference between the experimental and control groups (p = 0.002 < 0.05), so it can be concluded that the constructivism-based experimental method is more effective than conventional learning in improving student creativity and learning outcomes.